A kind of anti-shedding water-resistant ceramic and its preparation process

By using specific ceramic raw materials and processes to form the ceramic blank with an inner groove structure and perform surface coating, the problems of easy falling off of ceramic laying and waste recycling are solved, and the high water resistance and antibacterial properties of ceramics are achieved.

CN118745108BActive Publication Date: 2025-02-18JIANGXI JINLIYUAN CERAMICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410737277.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-07
Publication Date
2025-02-18
Estimated Expiration
2044-06-07

AI Technical Summary

Technical Problem

Ceramics are prone to fall off after laying, and it is difficult to recycle and utilize ceramic waste. How to improve the water resistance and bonding properties of ceramics?

Method used

Sodium feldspar, black soil, Xikeng mud, ball soil, talc, quartz sand, bauxite, and waste porcelain powder are used as ceramic raw materials, and ceramic blanks with inner groove structure are formed by ball milling, spray granulation and dry press forming. and surface coating is carried out using vinyl acetate, butyl acrylate and acrylamide copolymer emulsion, styrene acrylic emulsion and antibacterial liquid to improve the antibacterial properties of ceramics.

Benefits of technology

It improves the mechanical properties and water resistance of ceramics, enhances the binding properties of ceramics and cement-based binders, realizes the recycling of waste porcelain powder, and improves the antibacterial properties of ceramics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118745108B_ABST
    Figure CN118745108B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of waterproof ceramics, and specifically to an anti-shedding and water-resistant ceramic and a preparation process thereof. The present invention uses albite, black clay, Xikeng mud, ball clay, burnt talc, quartz sand, bauxite, and waste porcelain powder as ceramic raw materials to fire a ceramic body. The scheme recycles the waste porcelain powder and adjusts the formula dosage of the body. The prepared ceramic body has excellent mechanical properties and improved strength, and the water absorption rate of the ceramic is low and the water resistance is excellent. On the basis of this scheme, the present application uses vinyl acetate, butyl acrylate and acrylamide to prepare a copolymer emulsion, and mixes the copolymer emulsion, styrene acrylic emulsion and antibacterial liquid, and coats the surface of the ceramic body to improve the antibacterial performance of the ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waterproof ceramics, in particular to an anti-shedding water-resistant ceramic and a preparation process thereof. Background Art

[0002] With the rapid development of the economy, the development of China's ceramic industry is becoming more and more prosperous. Correspondingly, the stacking and landfill recycling of ceramic waste has also become a topic of concern to us. How to recycle ceramic waste and use it as raw material for ceramic preparation to reduce solid waste pollution is a technical problem that urgently needs to be solved.

[0003] At the same time, ceramics are prone to falling off after paving, and the bonding performance of cement-based adhesive materials and ceramics is also an issue we focus on. Based on this situation, this application discloses an anti-falling water-resistant ceramic and its preparation process, and adjusts and improves the processing and paving process of ceramics. Summary of the invention

[0004] The object of the present invention is to provide a debonding-resistant water-resistant ceramic and a preparation process thereof, so as to solve the problems raised in the above-mentioned background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a preparation process of anti-shedding water-resistant ceramics, comprising the following steps:

[0006] Step (1): mixing ceramic raw materials and water glass, ball milling to form a slurry, spray granulation, dry pressing to form a body with an inner groove on one side, and sintering at a high temperature to obtain a ceramic matrix;

[0007] Step (2): mixing polyvinyl alcohol and deionized water, stirring at 85-90°C until dissolved, cooling to 65-70°C, adding an emulsifier and 1 / 4 mass part of an initiator, stirring evenly, heating to 75-80°C, adding a reaction monomer, keeping the temperature for reaction for 1-2 hours, then adding the remaining initiator and reaction monomer, continuing the reaction for 2-3 hours, cooling to 50-60°C, adding a saturated sodium bicarbonate solution to adjust the pH, filtering the material, and obtaining a copolymer emulsion with a solid content of 30-40%; the reaction monomers include vinyl acetate, butyl acrylate and acrylamide in a mass ratio of 7:2:1;

[0008] Step (3): Mix the copolymer emulsion and the styrene acrylic emulsion, add the antibacterial liquid, and stir for 20 to 30 minutes to obtain a coating liquid; apply the coating liquid to the surface of the ceramic substrate, and vacuum dry to obtain a water-resistant ceramic.

[0009] In a more optimized solution, in step (1), the components of the ceramic raw materials include: by weight, 5-10 parts of albite, 5-10 parts of black clay, 20-25 parts of Xikeng mud, 25-30 parts of ball clay, 1-3 parts of burned talc, 3-5 parts of quartz sand, 1-2 parts of bauxite, and 25-30 parts of waste porcelain powder; the amount of water glass used is 0.3wt%~0.5wt% of the total mass of the ceramic raw materials.

[0010] In a more optimized solution, in step (1), the mass ratio of material: ball: water during ball milling is 1:2:0.45, the ball milling speed is 400-500 r / min, and the ball milling time is 40-50 min; the pressure during dry pressing is 12 MPa, the sintering temperature is 1200-1250°C, the time is 50-60 min, and the heating rate is 10°C / min.

[0011] In a more optimized solution, in step (1), the inner groove is inclined outward, the height of the inner groove is 1.5-2 mm, and the length of the inner groove is 0.3-0.5 mm; a plurality of inner grooves are arranged equidistantly and periodically on the surface of the blank, the inclination directions of adjacent inner grooves are opposite, and the spacing is 1-2 mm.

[0012] In a more optimized solution, in step (2), the amount of polyvinyl alcohol used is 3wt%~4wt% of the total mass of the reaction monomers; the initiator is ammonium persulfate, and the amount of ammonium sulfate used is 0.9wt%~1wt% of the total mass of the reaction monomers; the emulsifier is a mixture of sodium dodecyl sulfate and OP-10, with a mass ratio of 1:1, and the total amount of emulsifier used is 2wt%~3wt% of the total mass of the reaction monomers.

[0013] In a more optimized solution, in step (3), the proportion of the copolymer emulsion in the coating liquid is 60wt%~65wt%, and the proportion of the antibacterial liquid is 6wt%~10wt%; the coating thickness of the coating liquid is 0.5~1mm.

[0014] In a more optimized solution, in step (3), the preparation steps of the antibacterial liquid are: mixing nanosilver, sodium dodecyl sulfate and deionized water, stirring evenly to obtain the antibacterial liquid; the mass ratio of the nanosilver to sodium dodecyl sulfate is 10:1; and the solid content of the nanosilver in the antibacterial liquid is 0.2-0.3 mg / mL.

[0015] A more optimized solution is a water-resistant ceramic prepared according to any of the preparation processes described above.

[0016] A more optimized solution is the application of water-resistant ceramics disclosed in this solution. During the construction of the water-resistant ceramics, a cement-based adhesive is first applied to the wall surface, and then the water-resistant ceramics are laid. The preparation steps of the cement-based adhesive are: cement, quartz sand, calcium carbonate and cellulose ether are mixed, kaolin, calcium formate, wood fiber, copolymer emulsion and styrene-acrylic emulsion are added, and stirred evenly to obtain cement material, and water is added to the cement material and stirred evenly to obtain a cement-based adhesive.

[0017] For the more optimized solution, the dosage of each component is: by mass, 28-32 parts of cement, 45-50 parts of quartz sand, 8-10 parts of calcium carbonate, 0.4-0.6 parts of cellulose ether, 4-5 parts of metakaolin, 0.3-0.5 parts of calcium formate, 0.3-0.5 parts of wood fiber, 2-4 parts of copolymer emulsion, 3-5 parts of styrene-acrylic emulsion, and 15-20 parts of water.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] The invention discloses a preparation process of anti-shedding water-resistant ceramics. The scheme uses albite, black clay, Xikeng mud, ball clay, burned talc, quartz sand, bauxite and waste porcelain powder as ceramic raw materials to fire a ceramic green body. The scheme recycles the waste porcelain powder and adjusts the formula and dosage of the green body. The prepared ceramic green body has excellent mechanical properties and improved strength, and the water absorption rate of the ceramic is low and the water resistance is excellent. On the basis of this scheme, the application uses vinyl acetate, butyl acrylate and acrylamide to prepare a copolymer emulsion, and the copolymer emulsion, styrene acrylic emulsion and antibacterial liquid are mixed and coated on the surface of the ceramic green body to improve the antibacterial property of the ceramic.

[0020] When laying existing ceramics, cement-based mortar is generally applied on the wall as a bonding material, and then the ceramics are laid. Therefore, in order to prevent the ceramics from falling off, this solution defines the inner structure of the ceramic body, specifically "the inner groove is inclined outward, the height of the inner groove is 1.5~2mm, and the length of the inner groove is 0.3~0.5mm; a number of inner grooves are equidistantly arranged periodically on the surface of the body, the inclination directions of adjacent inner grooves are opposite, and the interval distance is 1~2mm", that is, an inner groove is provided on one side of the ceramic. This structure can improve the bonding performance between the cement-based mortar and the ceramic. In actual application, the inclination direction and number of the inner grooves can be adjusted according to actual needs.

[0021] On this basis, in order to further improve the bonding performance between ceramics and cement-based mortar, this scheme uses copolymer emulsion and styrene-acrylic emulsion to modify the mortar, and adjusts the formula to "28-32 parts of cement, 45-50 parts of quartz sand, 8-10 parts of calcium carbonate, 0.4-0.6 parts of cellulose ether, 4-5 parts of metakaolin, 0.3-0.5 parts of calcium formate, 0.3-0.5 parts of wood fiber, 2-4 parts of copolymer emulsion, 3-5 parts of styrene-acrylic emulsion, and 15-20 parts of water". The cement-based adhesive made with this formula has high bonding strength with ceramics. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0023] Figure 1 It is a schematic diagram of the combination of the water-resistant ceramic and cement-based binder disclosed in the present invention. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] In this embodiment, the preparation steps of the antibacterial liquid are: mixing nanosilver, sodium dodecyl sulfate and deionized water, stirring evenly to obtain the antibacterial liquid; the mass ratio of the nanosilver to the sodium dodecyl sulfate is 10:1; the solid content of the nanosilver in the antibacterial liquid is 0.2 mg / mL.

[0026] The polyvinyl alcohol is PVA1788; the styrene acrylic emulsion model is RS300S. The Xikeng mud contains 68wt% of silicon dioxide, 25.4wt% of aluminum oxide, 2.1wt% of aluminum oxide, 3.6wt% of potassium oxide, 0.2wt% of calcium oxide, 0.25wt% of magnesium oxide, and the rest is titanium oxide. The cement is P.O42.5 cement; the quartz sand particle size is 40~50 mesh; the cellulose ether is 30011C cellulose ether; and the wood fiber is PWC500. The particle size of nanosilver is 40~50nm.

[0027] Embodiment 1: A process for preparing anti-shedding water-resistant ceramics, comprising the following steps:

[0028] Step (1): mixing ceramic raw materials and water glass, ball milling to form a slurry, spray granulation, dry pressing to form a body with an inner groove on one side, and sintering at a high temperature to obtain a ceramic matrix;

[0029] The ceramic raw material components include: by weight, 8 parts of albite, 8 parts of black clay, 22 parts of Xikeng mud, 30 parts of ball clay, 2 parts of burnt talc, 5 parts of quartz sand, 1 part of bauxite, and 28 parts of waste porcelain powder; the amount of water glass is 0.4wt% of the total weight of the ceramic raw materials. During ball milling, the mass ratio of material: ball: water is 1:2:0.45, the ball milling speed is 400r / min, and the ball milling time is 40min; during dry pressing, the pressure is 12MPa, the firing temperature is 1200℃, the time is 60min, and the heating rate is 10℃ / min.

[0030] The inner groove is inclined outward, the height of the inner groove is 1.5 mm, and the length of the inner groove is 0.5 mm; a plurality of inner grooves are arranged equidistantly and periodically on the surface of the blank, and the inclination directions of adjacent inner grooves are opposite, and the distance between them is 1.5 mm. Figure 1 shown.

[0031] Step (2): polyvinyl alcohol and deionized water are mixed, stirred at 85°C until dissolved, cooled to 65°C, an emulsifier and 1 / 4 mass part of an initiator are added, stirred evenly, heated to 75°C, a reaction monomer is added, and the reaction is kept warm for 2 hours, and then the remaining initiator and reaction monomer are added, and the reaction is continued for 2 hours, cooled to 50°C, a saturated sodium bicarbonate solution is added to adjust the pH, and the material is filtered to obtain a copolymer emulsion with a solid content of 40%; the reaction monomers include vinyl acetate, butyl acrylate and acrylamide in a mass ratio of 7:2:1.

[0032] The amount of polyvinyl alcohol used is 3wt% of the total mass of the reaction monomers; the initiator is ammonium persulfate, and the amount of ammonium sulfate used is 1wt% of the total mass of the reaction monomers; the emulsifier is a compound of sodium dodecyl sulfate and OP-10, with a mass ratio of 1:1, and the total amount of emulsifier used is 2.5wt% of the total mass of the reaction monomers.

[0033] Step (3): 65 g of copolymer latex and 27 g of styrene acrylic latex were mixed, 8 g of antibacterial liquid was added, and stirred for 20 min to obtain a coating liquid; the coating liquid was applied to the surface of the ceramic substrate, and vacuum dried to obtain a water-resistant ceramic. The coating thickness of the coating liquid was 0.8 mm.

[0034] Embodiment 2: A process for preparing anti-shedding water-resistant ceramics, comprising the following steps:

[0035] Step (1): mixing ceramic raw materials and water glass, ball milling to form a slurry, spray granulation, dry pressing to form a body with an inner groove on one side, and sintering at a high temperature to obtain a ceramic matrix;

[0036] The ceramic raw material components include: by weight, 8 parts of albite, 8 parts of black clay, 22 parts of Xikeng mud, 30 parts of ball clay, 2 parts of burnt talc, 5 parts of quartz sand, 1 part of bauxite, and 29 parts of waste porcelain powder; the amount of water glass is 0.4wt% of the total weight of the ceramic raw materials. During ball milling, the mass ratio of material: ball: water is 1:2:0.45, the ball milling speed is 400r / min, and the ball milling time is 45min; during dry pressing, the pressure is 12MPa, the firing temperature is 1200℃, the time is 55min, and the heating rate is 10℃ / min.

[0037] The inner groove is inclined outward, the height of the inner groove is 1.5 mm, and the length of the inner groove is 0.5 mm; a plurality of inner grooves are arranged equidistantly and periodically on the surface of the blank, and the inclination directions of adjacent inner grooves are opposite, and the distance between them is 1.5 mm. Figure 1 shown.

[0038] Step (2): polyvinyl alcohol and deionized water are mixed, stirred at 85°C until dissolved, cooled to 70°C, an emulsifier and 1 / 4 mass part of an initiator are added, stirred evenly, heated to 75°C, a reaction monomer is added, and the reaction is kept warm for 1.5 hours, and then the remaining initiator and reaction monomer are added, and the reaction is continued for 2.5 hours, cooled to 55°C, a saturated sodium bicarbonate solution is added to adjust the pH, and the material is filtered to obtain a copolymer emulsion with a solid content of 40%; the reaction monomers include vinyl acetate, butyl acrylate and acrylamide in a mass ratio of 7:2:1.

[0039] The amount of polyvinyl alcohol used is 3wt% of the total mass of the reaction monomers; the initiator is ammonium persulfate, and the amount of ammonium sulfate used is 1wt% of the total mass of the reaction monomers; the emulsifier is a compound of sodium dodecyl sulfate and OP-10, with a mass ratio of 1:1, and the total amount of emulsifier used is 2.5wt% of the total mass of the reaction monomers.

[0040] Step (3): 65 g of copolymer emulsion and 27 g of styrene-acrylic emulsion were mixed, 8 g of antibacterial liquid was added, and stirred for 25 min to obtain a coating liquid; the coating liquid was applied to the surface of the ceramic substrate, and vacuum dried to obtain a water-resistant ceramic. The coating thickness of the coating liquid was 0.8 mm.

[0041] Embodiment 3: A process for preparing anti-shedding water-resistant ceramics, comprising the following steps:

[0042] Step (1): mixing ceramic raw materials and water glass, ball milling to form a slurry, spray granulation, dry pressing to form a body with an inner groove on one side, and sintering at a high temperature to obtain a ceramic matrix;

[0043] The ceramic raw material components include: by weight, 8 parts of albite, 8 parts of black clay, 22 parts of Xikeng mud, 30 parts of ball clay, 2 parts of calcined talc, 5 parts of quartz sand, 1 part of bauxite, and 30 parts of waste porcelain powder; the amount of water glass is 0.4wt% of the total weight of the ceramic raw materials. During ball milling, the mass ratio of material: ball: water is 1:2:0.45, the ball milling speed is 400r / min, and the ball milling time is 45min; during dry pressing, the pressure is 12MPa, the firing temperature is 1200℃, the time is 55min, and the heating rate is 10℃ / min.

[0044] The inner groove is inclined outward, the height of the inner groove is 1.5 mm, and the length of the inner groove is 0.5 mm; a plurality of inner grooves are arranged equidistantly and periodically on the surface of the blank, and the inclination directions of adjacent inner grooves are opposite, and the distance between them is 1.5 mm. Figure 1 shown.

[0045] Step (2): polyvinyl alcohol and deionized water are mixed, stirred at 85°C until dissolved, cooled to 70°C, an emulsifier and 1 / 4 mass part of an initiator are added, stirred evenly, heated to 80°C, a reaction monomer is added, the reaction is kept warm for 2 hours, the remaining initiator and reaction monomer are added, the reaction is continued for 2 hours, the temperature is cooled to 55°C, a saturated sodium bicarbonate solution is added to adjust the pH, the material is filtered, and a copolymer emulsion with a solid content of 40% is obtained; the reaction monomers include vinyl acetate, butyl acrylate and acrylamide in a mass ratio of 7:2:1.

[0046] The amount of polyvinyl alcohol used is 3wt% of the total mass of the reaction monomers; the initiator is ammonium persulfate, and the amount of ammonium sulfate used is 1wt% of the total mass of the reaction monomers; the emulsifier is a compound of sodium dodecyl sulfate and OP-10, with a mass ratio of 1:1, and the total amount of emulsifier used is 2.5wt% of the total mass of the reaction monomers.

[0047] Step (3): 65 g of copolymer emulsion and 27 g of styrene-acrylic emulsion were mixed, 8 g of antibacterial liquid was added, and stirred for 30 min to obtain a coating liquid; the coating liquid was applied to the surface of the ceramic substrate, and vacuum dried to obtain a water-resistant ceramic. The coating thickness of the coating liquid was 0.8 mm.

[0048] Comparative Example 1: Example 3 was used as a control group, and no inner groove was provided in Comparative Example 1.

[0049] A preparation process of anti-shedding water-resistant ceramics comprises the following steps:

[0050] Step (1): mixing ceramic raw materials and water glass, ball milling to form a slurry, spray granulation, dry pressing to form a body without inner grooves, and high temperature firing to obtain a ceramic matrix;

[0051] The ceramic raw material components include: by weight, 8 parts of albite, 8 parts of black clay, 22 parts of Xikeng mud, 30 parts of ball clay, 2 parts of calcined talc, 5 parts of quartz sand, 1 part of bauxite, and 30 parts of waste porcelain powder; the amount of water glass is 0.4wt% of the total weight of the ceramic raw materials. During ball milling, the mass ratio of material: ball: water is 1:2:0.45, the ball milling speed is 400r / min, and the ball milling time is 45min; during dry pressing, the pressure is 12MPa, the firing temperature is 1200℃, the time is 55min, and the heating rate is 10℃ / min.

[0052] Step (2): polyvinyl alcohol and deionized water are mixed, stirred at 85°C until dissolved, cooled to 70°C, an emulsifier and 1 / 4 mass part of an initiator are added, stirred evenly, heated to 80°C, a reaction monomer is added, the reaction is kept warm for 2 hours, the remaining initiator and reaction monomer are added, the reaction is continued for 2 hours, the temperature is cooled to 55°C, a saturated sodium bicarbonate solution is added to adjust the pH, the material is filtered, and a copolymer emulsion with a solid content of 40% is obtained; the reaction monomers include vinyl acetate, butyl acrylate and acrylamide in a mass ratio of 7:2:1.

[0053] The amount of polyvinyl alcohol used is 3wt% of the total mass of the reaction monomers; the initiator is ammonium persulfate, and the amount of ammonium sulfate used is 1wt% of the total mass of the reaction monomers; the emulsifier is a compound of sodium dodecyl sulfate and OP-10, with a mass ratio of 1:1, and the total amount of emulsifier used is 2.5wt% of the total mass of the reaction monomers.

[0054] Step (3): 65 g of copolymer emulsion and 27 g of styrene-acrylic emulsion were mixed, 8 g of antibacterial liquid was added, and stirred for 30 min to obtain a coating liquid; the coating liquid was applied to the surface of the ceramic substrate, and vacuum dried to obtain a water-resistant ceramic. The coating thickness of the coating liquid was 0.8 mm.

[0055] Comparative Example 2: Example 3 was used as the control group, and no antibacterial liquid was added to Comparative Example 2.

[0056] A preparation process of anti-shedding water-resistant ceramics comprises the following steps:

[0057] Step (1): mixing ceramic raw materials and water glass, ball milling to form a slurry, spray granulation, dry pressing to form a body with an inner groove on one side, and sintering at a high temperature to obtain a ceramic matrix;

[0058] The ceramic raw material components include: by weight, 8 parts of albite, 8 parts of black clay, 22 parts of Xikeng mud, 30 parts of ball clay, 2 parts of calcined talc, 5 parts of quartz sand, 1 part of bauxite, and 30 parts of waste porcelain powder; the amount of water glass is 0.4wt% of the total weight of the ceramic raw materials. During ball milling, the mass ratio of material: ball: water is 1:2:0.45, the ball milling speed is 400r / min, and the ball milling time is 45min; during dry pressing, the pressure is 12MPa, the firing temperature is 1200℃, the time is 55min, and the heating rate is 10℃ / min.

[0059] The inner groove is inclined outward, the height of the inner groove is 1.5 mm, and the length of the inner groove is 0.5 mm; a plurality of inner grooves are arranged equidistantly and periodically on the surface of the blank, and the inclination directions of adjacent inner grooves are opposite, and the distance between them is 1.5 mm.

[0060] Step (2): polyvinyl alcohol and deionized water are mixed, stirred at 85°C until dissolved, cooled to 70°C, an emulsifier and 1 / 4 mass part of an initiator are added, stirred evenly, heated to 80°C, a reaction monomer is added, the reaction is kept warm for 2 hours, the remaining initiator and reaction monomer are added, the reaction is continued for 2 hours, the temperature is cooled to 55°C, a saturated sodium bicarbonate solution is added to adjust the pH, the material is filtered, and a copolymer emulsion with a solid content of 40% is obtained; the reaction monomers include vinyl acetate, butyl acrylate and acrylamide in a mass ratio of 7:2:1.

[0061] The amount of polyvinyl alcohol used is 3wt% of the total mass of the reaction monomers; the initiator is ammonium persulfate, and the amount of ammonium sulfate used is 1wt% of the total mass of the reaction monomers; the emulsifier is a compound of sodium dodecyl sulfate and OP-10, with a mass ratio of 1:1, and the total amount of emulsifier used is 2.5wt% of the total mass of the reaction monomers.

[0062] Step (3): 65 g of copolymer emulsion and 27 g of styrene acrylic emulsion were mixed and stirred for 30 min to obtain a coating liquid; the coating liquid was applied to the surface of the ceramic substrate and vacuum dried to obtain a water-resistant ceramic. The coating thickness of the coating liquid was 0.8 mm.

[0063] Comparative Example 3: Example 3 was used as a control group, and no surface coating was performed in Comparative Example 3.

[0064] A preparation process of anti-shedding water-resistant ceramics comprises the following steps:

[0065] Step (1): Ceramic raw materials and water glass are mixed, ball-milled to form a slurry, spray-granulated, dry-pressed to form a body with an inner groove on one side, and fired at a high temperature to obtain a water-resistant ceramic.

[0066] The ceramic raw material components include: by weight, 8 parts of albite, 8 parts of black clay, 22 parts of Xikeng mud, 30 parts of ball clay, 2 parts of calcined talc, 5 parts of quartz sand, 1 part of bauxite, and 30 parts of waste porcelain powder; the amount of water glass is 0.4wt% of the total weight of the ceramic raw materials. During ball milling, the mass ratio of material: ball: water is 1:2:0.45, the ball milling speed is 400r / min, and the ball milling time is 45min; during dry pressing, the pressure is 12MPa, the firing temperature is 1200℃, the time is 55min, and the heating rate is 10℃ / min.

[0067] The inner groove is inclined outward, the height of the inner groove is 1.5 mm, and the length of the inner groove is 0.5 mm; a plurality of inner grooves are arranged equidistantly and periodically on the surface of the blank, and the inclination directions of adjacent inner grooves are opposite, and the distance between them is 1.5 mm.

[0068] Embodiment 4: The specific process of laying water-resistant ceramics is as follows:

[0069] Step A: Cement, quartz sand, calcium carbonate and cellulose ether are mixed, and metakaolin, calcium formate, wood fiber, copolymer emulsion and styrene acrylic emulsion are added, and stirred evenly to obtain cement material, and water is added to the cement material and stirred evenly to obtain a cement binder.

[0070] The amount of each component is: by mass, 29 parts of cement, 48 parts of quartz sand, 10 parts of calcium carbonate, 0.5 parts of cellulose ether, 5 parts of metakaolin, 0.5 parts of calcium formate, 0.5 parts of wood fiber, 3 parts of copolymer emulsion, 5 parts of styrene-acrylic emulsion, and 20 parts of water.

[0071] Step B: Apply cement-based adhesive to the standard concrete slab for testing and lay water-resistant ceramic.

[0072] Detection experiment:

[0073] 1. Take the water-resistant ceramics prepared in Examples 1 to 3 and Comparative Examples 1 to 2 and test their properties:

[0074] Water resistance: Dry the ceramic at 105℃ for 4 hours, weigh it after cooling, immerse it in distilled water, heat it to boiling, boil it for 3 hours, wipe off the surface dripping liquid beads after cooling, weigh it again, record the data and calculate the water absorption rate.

[0075] Bending strength: The bending strength at room temperature was tested using a universal testing machine. The size of the test sample was 3mm×4mm×40mm. The bending strength was tested using the three-point bending method. The loading speed was 0.5mm / min.

[0076] Antibacterial performance: The antibacterial property was tested according to the method disclosed in JC / T897-2014, and the test bacteria was Escherichia coli.

[0077] 2. Take the water-resistant ceramics prepared in Examples 1 to 3 and Comparative Examples 1 to 2, and prepare a cement-based binder by the method disclosed in Example 4, wherein the size of the concrete slab is 400 mm × 200 mm × 40 mm, the size of the ceramic is 50 mm × 50 mm, and the thickness is 7 mm, which meets the JC / T547-2017 standard, and the tensile bond strength is tested according to the method disclosed in JC / T547-2017.

[0078]

[0079] Conclusion: The present invention discloses a preparation process of anti-shedding water-resistant ceramics. The scheme uses albite, black clay, Xikeng mud, ball clay, burned talc, quartz sand, bauxite, and waste porcelain powder as ceramic raw materials to fire ceramic green bodies. The scheme recycles the waste porcelain powder and adjusts the formula and dosage of the green body. The prepared ceramic green body has excellent mechanical properties and improved strength. The ceramic has low water absorption and excellent water resistance. On the basis of this scheme, the present application utilizes ternary copolymerization of vinyl acetate, butyl acrylate and acrylamide to prepare a copolymer emulsion, and mixes the copolymer emulsion, styrene-acrylic emulsion and antibacterial liquid, and coats the surface of the ceramic green body to improve the antibacterial properties of the ceramic.

[0080] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A process for preparing anti-shedding water-resistant ceramics, characterized in that: The following steps are involved: Step (1): mixing ceramic raw materials and water glass, ball milling to form a slurry, spray granulation, dry pressing to form a body with an inner groove on one side, and sintering at a high temperature to obtain a ceramic matrix; Step (2): mixing polyvinyl alcohol and deionized water, stirring at 85-90°C until dissolved, cooling to 65-70°C, adding an emulsifier and 1 / 4 mass part of an initiator, stirring evenly, heating to 75-80°C, adding a reaction monomer, keeping the temperature for reaction for 1-2 hours, then adding the remaining initiator and reaction monomer, continuing the reaction for 2-3 hours, cooling to 50-60°C, adding a saturated sodium bicarbonate solution to adjust the pH, filtering the material, and obtaining a copolymer emulsion with a solid content of 30-40%; the reaction monomers include vinyl acetate, butyl acrylate and acrylamide in a mass ratio of 7:2:1; Step (3): Mix the copolymer emulsion and the styrene acrylic emulsion, add the antibacterial liquid, and stir for 20 to 30 minutes to obtain a coating liquid; Applying the coating liquid to the surface of the ceramic substrate and vacuum drying to obtain a water-resistant ceramic; In step (1), the components of the ceramic raw materials include: by weight, 5-10 parts of albite, 5-10 parts of black clay, 20-25 parts of Xikeng mud, 25-30 parts of ball clay, 1-3 parts of calcined talc, 3-5 parts of quartz sand, 1-2 parts of bauxite, and 25-30 parts of waste porcelain powder; the amount of water glass used is 0.3wt%-0.5wt% of the total mass of the ceramic raw materials; In step (1), the inner groove is inclined outward, the height of the inner groove is 1.5-2 mm, and the length of the inner groove is 0.3-0.5 mm; a plurality of inner grooves are arranged equidistantly and periodically on the surface of the blank, the inclination directions of adjacent inner grooves are opposite, and the spacing is 1-2 mm; In step (3), the preparation steps of the antibacterial liquid are: mixing nano silver, sodium dodecyl sulfate and deionized water, and stirring them evenly to obtain the antibacterial liquid.

2. The process for preparing the anti-shedding water-resistant ceramic according to claim 1, characterized in that: In step (1), the ball milling speed is 400-500 r / min, and the ball milling time is 40-50 min; the pressure during dry pressing is 12 MPa, the sintering temperature is 1200-1250° C., and the time is 50-60 min.

3. The process for preparing the anti-shedding water-resistant ceramic according to claim 1, characterized in that: In step (2), the amount of polyvinyl alcohol used is 3wt%~4wt% of the total mass of the reaction monomers; the initiator is ammonium persulfate, and the amount of ammonium sulfate used is 0.9wt%~1wt% of the total mass of the reaction monomers; the emulsifier is a compound of sodium dodecyl sulfate and OP-10, the mass ratio is 1:1, and the total amount of emulsifier used is 2wt%~3wt% of the total mass of the reaction monomers.

4. The process for preparing the anti-shedding water-resistant ceramic according to claim 1, characterized in that: In step (3), the proportion of the copolymer emulsion in the coating liquid is 60wt%~65wt%, and the proportion of the antibacterial liquid is 6wt%~10wt%; the coating thickness of the coating liquid is 0.5~1mm.

5. A water-resistant ceramic prepared according to the preparation process according to any one of claims 1 to 4.

6. The use of the water-resistant ceramic according to claim 5, characterized in that: During the construction of water-resistant ceramics, a cement-based adhesive is first applied to the wall surface, and then the water-resistant ceramics are laid. The preparation steps of the cement-based adhesive are as follows: cement, quartz sand, calcium carbonate and cellulose ether are mixed, metakaolin, calcium formate, wood fiber, copolymer emulsion and styrene acrylic emulsion are added, and stirred evenly to obtain cement material, and water is added to the cement material and stirred evenly to obtain a cement-based adhesive.

7. The use of the water-resistant ceramic according to claim 6, characterized in that: The amount of each component is: by mass, 28-32 parts of cement, 45-50 parts of quartz sand, 8-10 parts of calcium carbonate, 0.4-0.6 parts of cellulose ether, 4-5 parts of metakaolin, 0.3-0.5 parts of calcium formate, 0.3-0.5 parts of wood fiber, 2-4 parts of copolymer emulsion, 3-5 parts of styrene-acrylic emulsion, and 15-20 parts of water.

Citation Information

Patent Citations

  • Environment-friendly wall surface interfacial agent and preparation method thereof

    CN106833177A

  • Sanitary ceramic and preparation method thereof

    CN112125644A